2014
DOI: 10.1080/13876988.2014.960227
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunications Infrastructure and Economic Growth: Comparative Policy Analysis for the G-20 Developed and Developing Countries

Abstract: This paper examines the nexus between the development of telecommunications infrastructure (DTI), economic growth, and four key indicators of the operations of advanced economies. It employs a panel vector auto-regressive model to detect causality and examine long-run relationships between variables in the G-20 countries for the period 2001-2012. Evidence is found that DTI, measured through six indicators, may cause economic growth and that causation may be bidirectional. Not surprisingly, the exact nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
3
10
0
5
Order By: Relevance
“…This is somewhat surprising given the prevalence of such studies in the traditional telecommunications policy literature. For example, the bidirectional relationship between Information Communication Technology infrastructure development and country-level economic performance is well-studied (Pradhan et al, 2014). Market concentration is a well-known factor in fixed and mobile service development and diffusion (Wallsten, 2001;Houpis et al, 2016).…”
Section: Internet Protocol Version 6 Adoption and Macrosocial Variablesmentioning
confidence: 99%
“…This is somewhat surprising given the prevalence of such studies in the traditional telecommunications policy literature. For example, the bidirectional relationship between Information Communication Technology infrastructure development and country-level economic performance is well-studied (Pradhan et al, 2014). Market concentration is a well-known factor in fixed and mobile service development and diffusion (Wallsten, 2001;Houpis et al, 2016).…”
Section: Internet Protocol Version 6 Adoption and Macrosocial Variablesmentioning
confidence: 99%
“…This is the first study to give evidence that ICT's positive returns to productivity have been reported both for the developed world and the developing world. Pradhan et al (2014) has examined the nexus between the development of modern telecommunication infrastructure (DTI) and economic growth in the G-20 countries for the period 2001-2012 and found that DTI (telephone, Internet, and broadband usage) would promote economic growth. The role of telecommunication service including fixed-line and mobile telephone on economic growth has been investigated, and the result revealed that mobile services contribute much more to growth compared with fixed-line service (Ward and Zheng (2016)).…”
Section: Ict Investment and Economic Growthmentioning
confidence: 99%
“…A number of academics in economic field have researched the role that ICT can play to fight poverty and catalyze socioeconomic development and growth (Bojnec & Fertő, ; Pradhan, Arvin, Bahmani, & Norman, ; Prieger, ; Rajabiun & Middleton, ; Ward & Zheng, ). Logically, the penetration of ICT could produce multiplier effect of investment, increasing employment, lowering transaction costs, improving marketing information, and accelerating diffusion of information, which has a significant positive effect on economic growth.…”
Section: Ict Investment and Economic Growthmentioning
confidence: 99%
“…Hasil penelitian ini sesuai dengan pendapat yang dikemukakan oleh Pradhan , et all (2014), yang berjudul Telecommunication Infrastructure and Economic Growth : Comparative Policy Analysis for the G-20 Developed and Developing Countriies yang menggunakan data selama periode 2001-2012, bahwa pengguna telepon seluler memiliki hubungan kausalitas satu arah dengan pertumbuhan ekonomi di G-20 negara.…”
Section: Kausalitas Antara Pengguna Telepon Seluler Dan Pertumbuhan Ekonomi DI Aseanunclassified
“…Berbagai penelitian telah dilkukan oleh beberapa peneliti terkait dengan kondisi teknologi informasi dan komunikasi (TIK) di berbegai negara. berdasarkan penelitian yang dilakukan dengan diperoleh hasil bahwa adanya hubungan kausalitas granger antara pengguna broadband, pengguna internet dan pertumbuhan ekonomi di G-20 Negara (Pradhan, et all;2018), hubungan positif dan signifikan antara infrastruktur TIK dan pertumbuhan ekonomi di Indonesia (Ahmad, 2015), pengaruh positif dan signifikan antara pengguna telepon tetap, pengguna telepon seluler dan GDP dalam jangka pendek maupun jangka panjang, sedangkan pengguna internet hanya dan GDP hanya berpengaruh positf dan signifikan dalam jangka panjang di Indonesia (Widias, 2011), hubungan kausalitas satu arah antara pengguna telepon seluler dan pertumbuhan ekonomi di negara berpendapatan tinggi (Saidi dan Mongi, 2018) adanya hubungan satu arah antara pengguna telepon tetap dan pertumbuhan ekonomi di negara Amerika Latin dan Asia (Cordeiro, 2008) Perkembangan teknologi merupakan salah satu pendorong bagi negaranegara ASEAN untuk mencapai kinerja ekonomi yang luar biasa. Pembuat kebijakan di negara-negara ASEAN telah menunjukkan ketertarikan yang besar terhadap peningkatan infrastruktur TIK.…”
unclassified